Penguatan Literasi Keuangan Generasi Muda Melalui Pemanfaatan Financial Technology - Faisol Faisol; Moh. Syarif; Merie Satya Angraini; Dina Alafi Hidayatin (Jurusan Akuntansi Universitas Trunojoyo Madura, 2026)
This community service initiative aims to enhance the financial literacy understanding and awareness of students at SMKS Darussalam Torjun Sampang through the wise and productive use of financial technology. The program was implemented using an educational and participatory approach that actively engaged students in the learning process. The results indicate that the financial literacy enhancement program, utilizing financial technology, was effective and had a positive impact on improving students’ understanding. Evaluation results showed a significant increase between pre-test and post-test scores, where the average initial score of 55 increased to 82 after the activity, a rise of 27 points or approximately 49%. Thus, this program not only impacts knowledge improvement but also has the potential to foster wiser and more responsible financial behavior among the younger generation.